Experimental evaluation of the diagonal tension test of hollow clay blocks strengthening with (AR) glass fibers - Delaram Ostad; Jalil Shafaei; Farshid Jandaghi Alaee (Case Studies in Construction Materials)
In many developing countries, masonry infill walls are commonly constructed using hollow clay blocks. Buildings incorporating these infill walls are particularly vulnerable to seismic loads due to the absence of adequate lateral load-resisting elements. Their poor performance during past earthquakes has resulted in irreparable structural damage and significant human casualties. Therefore, strengthening these infill walls is essential to improving the seismic safety and stability of buildings in earthquake-prone regions. Since shear capacity and ductility are key factors influencing the seismic performance of masonry infill walls, evaluating their shear behaviour under diagonal tension provides essential insight into their structural response during earthquakes. To investigate this, an experimental program comprising 33 diagonal tension tests was conducted on masonry wallettes with nominal dimensions of 650 × 650 × 100 mm. The tests focused on evaluating the shear performance of specimens under three conditions: (1) control specimens (unreinforced wallettes), (2) specimens strengthening with cement and plaster coatings, and (3) specimens strengthening with alkali-resistant (AR) glass fibers in combination with cement and plaster coatings. One-sided, double-sided, and combined coating configurations were employed. All tension tests were conducted in accordance with ASTM E519. Key evaluated parameters included force–displacement behaviour, shear stress–shear strain response, ductility, energy absorption (toughness), and shear modulus. The results revealed that specimens strengthening with (AR) glass fibers exhibited significant improvements in both load-carrying capacity and deformation characteristics. In particular, wallettes strengthening with cement mortar and AR-glass fibers demonstrated up to a 512 % increase in shear strength compared to the control specimens. These findings underscore the importance of fiber-reinforced systems in enhancing the shear strength of masonry infill walls and highlight their potential in improving structural performance and reducing seismic vulnerability in both new and existing buildings.